The problem of assessing the adaptive capacity of the human operator - E. P. Popechitelev; Ya. S. Pekker; T. V. Novikova (Бюллетень сибирской медицины)
Decomposition of professional thinking of the human operator in process control, requiring intense attention for a long time, was performed. The problem of assessing the ability of the operator to adapt to mental stress was formulated. The authors proposed a model for calculation of the indicators of the functional state of the body  during the transition from normal to hard work. It is based on a dynamic model of the system, which is not in a stationary state under external forces, but will be changing until the rate of entropy production within the system reaches the minimum in these conditions. It is shown that this model can be used to solve the problem.